2016
DOI: 10.1136/neurintsurg-2015-012231
|View full text |Cite
|
Sign up to set email alerts
|

Does the use of IV tPA in the current era of rapid and predictable recanalization by mechanical embolectomy represent good value?

Abstract: As healthcare delivery in the USA transforms into a model that at its core requires value-based considerations, ischemic stroke is confronted by intersecting forces. Modern techniques allow rapid revascularization in the majority of patients with large vessel occlusions. Dramatic advances in the evidentiary basis for mechanical embolectomy are increasing the number of patients treated with this therapy. A key part of the therapeutic arsenal in many patients treated with interventional techniques has been concu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
61
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(62 citation statements)
references
References 54 publications
0
61
0
1
Order By: Relevance
“…8,9 Important data about the prevalence of preinterventional reperfusion was extracted from the latest large randomized trials, as shown in a recently published metaanalysis, 11 suggesting the prevalence of preinterventional reperfusion to be ≈11%. Because of the heterogeneity of reported prevalences and insufficiently detailed reperfusion quality grading, 13,20 subgroup analyses and a systematic comparison with patients not having received tPA were not performed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Important data about the prevalence of preinterventional reperfusion was extracted from the latest large randomized trials, as shown in a recently published metaanalysis, 11 suggesting the prevalence of preinterventional reperfusion to be ≈11%. Because of the heterogeneity of reported prevalences and insufficiently detailed reperfusion quality grading, 13,20 subgroup analyses and a systematic comparison with patients not having received tPA were not performed.…”
Section: Discussionmentioning
confidence: 99%
“…These numbers increased to 13 (95% CI, [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] and 35 (95% CI, 18-464) when analysis was confined to M1 (proximal and distal) and ICA occlusions (SWIFT DIRECT trial cohort [Solitaire With the Intention for Thrombectomy Plus Intravenous t-PA Versus DIRECT Solitaire Stent-Retriever Thrombectomy in Acute Anterior Circulation Stroke], URL: http://www.clinicaltrials. gov.…”
Section: Number Needed To Treatmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of preprocedural IV rtPA on the rates of HT is of particular interest, as there is an ongoing scientific debate on whether the bridging approach is of any benefit [46]. In particular, there are conflicting results about whether preinterventional IV rtPA actually increases the risk of HTs after ET or not [8,47,48,49,50,51].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent commentary entitled ‘Does the use of IV tPA in the current era of rapid and predictable recanalization by mechanical embolectomy represent good value?’,1 we considered the advantages and disadvantages of administering intravenous tissue plasminogen activator (IV tPA) in patients also eligible for mechanical embolectomy. This generated much discussion, underscoring the topical nature of the question.…”
mentioning
confidence: 99%